Лінійний варіаційний принцип в опуклій максимізації - Кацев, М.В.; Семенов, В.В. (Видавничий дім "Академперіодика" НАН України, 2007)
We prove that, for any convex, Lipschitz, and lsc function f defined on a weakly compact convex set X in a Banach space E and for any ε > 0, there is x*  E* with ||x*||E* < ε such that f + x* attains its supremum on X.